2023
DOI: 10.2196/53124
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Agile Values in Software Engineering for Agility in Breast Cancer Treatment: Protocol for a Comparative Study

Yousra Odeh,
Mahmoud Al-Balas

Abstract: Background Breast cancer treatment has been described as a dynamic and patient-centered approach that emphasizes adaptability and flexibility throughout the treatment process. Breast cancer is complex, with varying subtypes and stages, making it important to tailor treatment plans to each patient’s unique circumstances. Breast cancer treatment delivery relies on a multidisciplinary team of health care professionals who collaborate to provide personalized care and quick adaptation to changing condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…In this research, agility was focused around the principles where agility values are identified as out of the scope, as it has been already addressed in recently published work. 170 Referring to the results in Results, it is apparent that the proposed 12 BCT agility principles conform to the agility notion as overall (ie, shown in resulting seven principles meeting agility where the five partially do). None of the proposed principles is recorded as not meeting agility.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this research, agility was focused around the principles where agility values are identified as out of the scope, as it has been already addressed in recently published work. 170 Referring to the results in Results, it is apparent that the proposed 12 BCT agility principles conform to the agility notion as overall (ie, shown in resulting seven principles meeting agility where the five partially do). None of the proposed principles is recorded as not meeting agility.…”
Section: Discussionmentioning
confidence: 83%
“…In this research, agility was focused around the principles where agility values are identified as out of the scope, as it has been already addressed in recently published work. 170 …”
Section: Discussionmentioning
confidence: 99%